EDUKASI 1000 HARI PERTAMA KEHIDUPAN UNTUK TINGKATKAN STATUS GIZI IBU HAMIL DAN ANAK DI KEDIRI - Sutrisni Sutrisni; Putri Wahyu Wigati2; Halimatus Saidah; Dhita Kris Prasetyanti; Galuh Pradian Yanuaringsih (Universitas Kadiri, 2026)
Based on data from the Kediri Regency Health Office in the Kediri Regency Health Profile 2024, the Ngasem Health Center recorded 248 stunted children out of 3,533 measured, representing 7.9%. This indicates that stunting remains a significant public health issue requiring promotive and preventive interventions, particularly through nutrition education for pregnant women, mothers of young children, and families during the First 1,000 Days of Life (HPK). This community service activity was conducted in Sukorejo Village, Ngasem District, Kediri Regency, with the aim of increasing community awareness of the importance of the First 1,000 Days of Life as a critical period for child growth and development. The program involved 20 participants, including pregnant women, breastfeeding mothers, and posyandu cadres. Activities consisted of interactive health education, group discussions, and demonstrations on preparing balanced meals using locally available food ingredients. Educational materials focused on the concept of the First 1,000 Days of Life, nutritional requirements during pregnancy and early childhood, and stunting prevention through a balanced diet. The results showed a substantial improvement in participants’ knowledge. Before the education session, 70% of participants had poor knowledge, while after the post-test, 95% demonstrated good understanding of HPK and appropriate nutritional practices. Participants also gained practical skills in preparing nutritious family meals. The program was well received and is expected to be implemented regularly to support sustainable stunting prevention efforts.